International consensus definitions of video signs of concussion in professional sports. Issue 20 (6th April 2019) - Davis, Gavin A; Makdissi, Michael; Bloomfield, Paul; Clifton, Patrick; Echemendia, Ruben J; Falvey, Éanna Cian; Fuller, Gordon Ward; Green, Gary; Harcourt, Peter; Hill, Thomas; McGuirk, Nathan; Meeuwisse, Willem; et al.
Abstract : Background: The use of video to assist professional sporting bodies with the diagnosis of sport-related concussion (SRC) has been well established; however, there has been little consistency across sporting codes with regards to which video signs should be used, and the definitions of each of these signs. Aim: The aims of this study were to develop a consensus for the video signs considered to be most useful in the identification of a possible SRC and to develop a consensus definition for each of these video signs across the sporting codes. Methods: A brief questionnaire was used to assess which video signs were considered to be most useful in the identification of a possible concussion. Consensus was defined as >90% agreement by respondents. Existing definitions of these video signs from individual sports were collated, and individual components of the definitions were assessed and ranked. A modified Delphi approach was then used to create a consensus definition for each of the video signs. Results: Respondents representing seven sporting bodies (Australian Football League, Cricket Australia, Major League Baseball, NFL, NHL, National Rugby League, World Rugby) reached consensus on eight video signs of concussion. Thirteen representatives from the seven professional sports ranked the definition components. Consolidation and refinement of the video signs and their definitions resulted in consensus definitions for six video signs of possible concussion: lying motionless, motor incoordination, impact seizure, tonic posturing, no protective action—floppy and blank/vacant look . Conclusions: These video signs and definitions have reached international consensus, are indicated for use by professional sporting bodies and will form the basis for further collaborative research.